Experience of the Absence of the Journey to Sessions in Clients' Narratives About Online Psychotherapy - Galasiński, Dariusz; Ziółkowska, Justyna; Witkowicz, Magdalena (Frontiers in Psychology, 2022)
Background Remotely provided psychotherapy due to the COVID-19 pandemic became common. One of the most significant changes related to providing online psychotherapy services is that clients no longer travel to their sessions. Aims In the article we are interested in the narrated experience of the absence of journey to psychotherapy sessions. We study clients' stories of past journeys and how their absence, resulting from the change of the mode of therapy provision, is coped with and replaced by other activities in their narratives. Methods The study takes a constructionist approach to discourse and focuses on the lexico-grammatical form of the notes. The data come from 12 semi-structured interviews with people who declared attending remote psychotherapy sessions after the national lockdown had been introduced. Results In the collected data, the physical journey is constructed not only as travel time, solitude which can be used for reflection, but, importantly, as an active process which ends with a resolution. In contrast, in narratives of the time before an online session, constructions of unfettered agents are replaced with those of people whose actions are hedged and qualified. Conclusion We argue that in the informants' narratives the journey to psychotherapy is meaningful and is part of the therapeutic process. We propose that it is a time of passing between two states—one before therapy and one in session. The journey therefore is experienced as a process of change, and not only a process of traveling.